2014
DOI: 10.1371/journal.pone.0111217
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Diagnostic Value of Contrast-Enhanced Breast MR Imaging and Mammography on Patients with BI-RADS 3–5 Microcalcifications

Abstract: ObjectiveTo retrospectively investigate the diagnostic value of breast MRI in patients with BI-RADS 3–5 microcalcifications in mammography.MethodsEighty-four patients with BI-RADS 3–5 microcalcifications on mammography underwent breast MR exams before surgical biopsy with a hookwire position under mammographic guidance. Two radiologists reviewed each lesion with BI-RADS by consensus. The diagnostic value of mammography and MRI was compared.ResultsHistopathological examination revealed 49 benign lesions and 42 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…As seen in our study, MRI imaging had a high degree of specificity in addition to high sensitivity. In a study by Li et al (28) and Warner et al (26) the specificity for MRI was estimated to be 95%, and to be 89% in the study by Keriege et al (25) The results of MRI in the present study for BIRADS 4-5 group showed both higher sensitivity and also specificity in comparison with ultrasonography. On this basis we can say that in the BIRADS 4-5 group, MRI was a more valuable diagnostic method than ultrasonography in diagnosing suspected lesions.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…As seen in our study, MRI imaging had a high degree of specificity in addition to high sensitivity. In a study by Li et al (28) and Warner et al (26) the specificity for MRI was estimated to be 95%, and to be 89% in the study by Keriege et al (25) The results of MRI in the present study for BIRADS 4-5 group showed both higher sensitivity and also specificity in comparison with ultrasonography. On this basis we can say that in the BIRADS 4-5 group, MRI was a more valuable diagnostic method than ultrasonography in diagnosing suspected lesions.…”
Section: Discussionsupporting
confidence: 43%
“…On this basis we can say that in the BIRADS 4-5 group, MRI was a more valuable diagnostic method than ultrasonography in diagnosing suspected lesions. However, Li et al (28) concluded that MRI has the best results in the group of patients with BIRADS 4 compared with other methods, but would not have better results than other methods in BIRADS 5. Similarly, Strobel et al (29) Also reported the best results for MRI in the BIRADS 4 group.…”
Section: Discussionmentioning
confidence: 99%
“…The main limitation of MRI in detection of DCIS is the fact that MRI was assessed only in patients with mammographic changes that were classified as suspicious microcalcifications. Thus, non calcified DCIS lesions were not evaluated, even though they might also show enhancement on MRI (20) .…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 is a summary of the study selection process according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Seven of the 20 studies were published during the past 2 years (6,(28)(29)(30)(33)(34)(35), while the oldest study dated from 1996 (20). Five studies included retrospective groups of patients (12,21,29,30,34), and the remaining 15 studies were prospective (5,6,10,20,22-28, [31][32][33]35).…”
Section: Study Design and Propertiesmentioning
confidence: 99%
“…All groups used a gadolinium-based contrast agent and a dedicated breast coil. Reader experience was either not declared (22,23,30) or varied substantially throughout the studies (5, 6,10,12,20,21,[24][25][26][27][28][29][31][32][33][34][35]. All MR imaging technical data are summarized in Table 1 and detailed QUADAS-2 assessment is illustrated in Figure 2.…”
Section: Study Design and Propertiesmentioning
confidence: 99%